2015
DOI: 10.4103/0975-7406.163571
|View full text |Cite
|
Sign up to set email alerts
|

Influence of erbium, chromium-doped: Yttrium scandium-gallium-garnet laser etching and traditional etching systems on depth of resin penetration in enamel: A confocal laser scanning electron microscope study

Abstract: Objective:This study was performed to assess the resin tag length penetration in enamel surface after bonding of brackets to identify which system was most efficient.Methodology:Our study was based on a more robust confocal microscopy for visualizing the resin tags in enamel. Totally, 100 extracted human first and second premolars have been selected for this study and were randomly divided into ten groups of 10 teeth each. In Group 1, the buccal enamel surface was etched with 37% phosphoric acid (3M ESPE), Gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 29 publications
2
5
0
1
Order By: Relevance
“…Kumar et al [23] used a lower output (1.5 W) to etch enamel, per Berks and colleagues, and observed that Er, Cr: YSGG laser irradiations using 1 W, 1.5 W or 2 W produced etching patterns similar to those produced by etching with acid in the scanning electron microscope (SEM) study. While Vijayan et al [48] found that the enamel surfaces etched by Er, Cr: YSGG laser at 1.5 W/20 Hz, 2 W/10 Hz and 2 W/20 Hz, 2 W/20 Hz provided the best results with consistency in tag lengths and other studies found that it provided adequate bond strength. Moreover, in vitro studies have shown that the same parameters could result in different outcomes and different parameters could result in similar outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Kumar et al [23] used a lower output (1.5 W) to etch enamel, per Berks and colleagues, and observed that Er, Cr: YSGG laser irradiations using 1 W, 1.5 W or 2 W produced etching patterns similar to those produced by etching with acid in the scanning electron microscope (SEM) study. While Vijayan et al [48] found that the enamel surfaces etched by Er, Cr: YSGG laser at 1.5 W/20 Hz, 2 W/10 Hz and 2 W/20 Hz, 2 W/20 Hz provided the best results with consistency in tag lengths and other studies found that it provided adequate bond strength. Moreover, in vitro studies have shown that the same parameters could result in different outcomes and different parameters could result in similar outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Laser irradiation on the dental surface can protect the enamel against the carious attack, which is one of its advantages. Nevertheless, the use of Er,Cr:YSGG laser when treating enamel surfaces and dentin has been presenting diverse results when it comes to dental adhesion [1][2][3][4].…”
Section: Resultsmentioning
confidence: 99%
“…There has been a growing research interest in the conditioning effects of erbium, chromium:yttrium-scandiumgallium-garnet (Er,Cr:YSGG) laser on tooth surfaces. The etching effects of Er,Cr:YSGG laser on dental hard tissues have been investigated mostly via microleakage evaluation and mechanical tests made on composite restorations applied to primary and permanent tooth cavities [4].…”
Section: Introductionmentioning
confidence: 99%
“…It causes surface roughening and irregularity similar to that of acid etching to a depth of 10 to 20 um, depending on the type of laser and the energy applied to the surface. [31] Thukral reported that ESEM analysis of enamel surface after Er.Cr.YSGG Laser irradiation showed the roughened enamel surfaces with intact morphology of the enamel prisms and complete absence of smear layer, so Laser-etching can be successfully used as an alternative to the conventional acid-etch. Skipping the step of acidetching also helps save chair-side time and the results of the laser etched tooth surface are superior or at least comparable to that of an acid etched tooth surface [32] .…”
Section: Discussionmentioning
confidence: 99%